The supply of skill and endogenous technical change: Evidence from a college expansion reform - Pedro M. Carneiro; Kai Liu; Kjell G. Salvanes (Centre for Microdata Methods and Practice (cemmap), 2018)
We examine the labor market consequences of an exogenous increase in the supply of skilled labor in several cities in Norway, resulting from the construction of new colleges in the 1970s. We find that skilled wages increased as a response, suggesting that along with an increase in the supply there was also an increase in demand for skill. We also show that college openings led to an increase in the productivity of skilled labor and investments in R&D. Our findings are consistent with models of endogenous technical change where an abundance of skilled workers may encourage firms to adopt skill-complementary technologies, leading to an upward-sloping long-run demand for skill.
Keywords: 330; Akademiker; Arbeitsnachfrage; Arbeitsangebotsverhalten; Endogenes Wachstumsmodell; Norwegen